Clinical and adipocytokine changes after bariatric surgery in morbidly obese women. (23rd July 2013) - Auguet, Teresa; Terra, Ximena; Hernández, Mercè; Sabench, Fàtima; Porras, Jose Antonio; Orellana‐Gavaldà, Josep Maria; Llutart, Jordi; Guiu‐Jurado, Esther; Berlanga, Alba; Martinez, Salomé; Aguilar, Carmen; Castillo, Daniel Del; et al.
Abstract : Objective: Recent studies report the effect of bariatric surgery on glycaemia control and prevention of type‐2‐diabetes in obese patients. This study is about the pathophysiological mechanisms associated to these changes. Design and Methods: Circulating levels of receptors of tumor necrosis factor (TNF‐RI, TNF‐RII), visfatin, high molecular weight (HMW) adiponectin, and C reactive protein (CRP) in 30 morbidly obese women (body mass index, BMI>40 kg/m 2 ) and 60 normal‐weight controls (BMI>25 kg/m 2 ) were analyzed. Morbidly obese were studied at three time‐points: before surgery (baseline), and 6 and 12 months after. Results: After surgery, the levels of TNF‐RI, TNF‐RII, visfatin, and CRP were significantly lower than its baseline levels, whereas HMW adiponectin was higher. Fasting glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA2‐IR) levels were markedly lower postoperatively. High density lipoproteins (HDL) moderately increased, and triglyceride levels had sharply decreased. The study of the predictive value of variables indicated that preoperative levels of TNF‐RI and visfatin correlated positively with levels of glucose, insulin, glycosylated hemoglobin A1c, and HOMA2‐IR postoperatively, whereas adiponectin levels correlated negatively. Baseline CRP levels negatively linked to HDL and TNF‐RII positively to triglyceride. Conclusions: The preoperative profile with high levels of proinflammatory adipocytokines is linked to smaller improvements in glucose homeostasis and lipid factors. The use of a range of biomarkers may predict the level of metabolic changes following bariatric surgery.